Evaluate the use of Recycled Asphalt Pavement (RAP) in the Construction of Roller Compacted Concret Pavement (RCC) - Yaser Bashkoul; Hassan Divandari (Salehan Institute of Higher Education, 2018)
One of the issues and problems of today's world is the massive amount of debris and trashes, especially asphalts resulting from the removal of worn-out pavements of urban roads. Recycled asphalt crumbs (RAP) are waste materials that certainly have significant undesirable effects on the surrounding environment. Given the properties reported by these materials, there are various ways to reuse these materials. One of the applications that has been considered by researchers is the use of these materials in cement mixtures, including concrete production. This is while a large amount of asphalt fragment is continuously produced in the repair and maintenance of roads. It is therefore desirable to be used in conventional mixtures used in construction of road pavements. In this regard, the present study investigates the use of recyclable asphalt materials in pavement roller shuttle (RCC) with the aim of reducing waste and its negative impacts on the environment. By examining the documentation and performing numerous experiments, it has been found that roller concrete made from recycled asphalt can be used as a suitable pavement for low traffic and rural roads, as well as for the final covering of a wide range of sidewalks.